SPEAKING STRATEGIES USED BY THE PROMINENT STUDENT AT SMK PGRI 3 MALANG - Raviona Annida (EDUCAFL : Journal of Education of English as Foreign Language, 2023)
Being an expert on English means mastering basic English skills. There are strategies used by students in order to make the students master English skills. One of the skills that must be learned is speaking. The participants are given some questions in the form of an open-ended interview by the researcher to identify prominent students’ English speaking strategies. The participants of this study were prominent students at SMK PGRI 3 Malang.The researcher used a qualitative method with a case study design in conducting this research. The research was conducted for a couple of weeks. The total of students who participate in this research was two prominent Students. The instruments of this study were Adopted from Quadir Mst. Moriam, Speaking Strategy Use by the EFL Students in Japan and Bangladesh, 2005. The data was validating used data triangulation. The study results show that the cognitive attribute is the most speaking strategy used by the prominent student. The application of the cognitive attributes affects the two prominent students in dominating speaking skills in English. The cognitive attributes also help the two prominent students learn the new vocabulary and some nice sounding or phrases to speak English easily.